Uncaria tomentosa (Willd.) DC. (Rubiaceae): Native species of Peru, herbal medicine recognized by traditional medicine - Valdiviezo-Campos, Juan Ernesto; Blanco-Olano, Cyntia Marysol; Olascuaga-Castillo, Karyn Alicia; Rubio-Guevara, Susana Del Rocio (Ethnobotany Research and Applications, 2020)
Background: Uncaria tomentosa (Will.) DC. It is known as "cat's claw", in traditional medicine it has anti-inflammatory, antiviral, immunostimulating and anti-tumor properties. They have bioactive pentacyclic and tetracyclic oxindole alkaloid type, as well as terpenes, flavonoids responsible for the therapeutic activity. The objective of this work reviews the botany, phytochemistry, obtaining, isolation and identification of bioactives, pharmacological activity and toxicity, medicinal properties and traditional uses regarding this species. Methods: Scientific database articles (Scopus, Scielo, academic Google) were compiled using keywords and connectors Uncaria tomentosa, ethnobotany, phytochemical, pharmacological activity, toxicity, medicinal properties, traditional use. Results: The search resulted in (457 in Scopus, 39 in Scielo and 8020 in academic google) between articles and related theses on the Uncaria tomentosa species, among them, 77 articles and theses of relevance for writing this review. Conclusions: Uncaria tomentosa shows its traditional use due to its important anti-inflammatory activity, this due to the oxindole pentacyclic alkaloid compounds that were described and supported by the scientific literature. This knowledge also fills a gap in the literature for the recognition of adulteration and, for the quality control of plant products and medicines from Uncaria tomentosa. Keywords: Native plant, Uncaria tomentosa, ethnobotany